In-vitro & in-vivo study of primary epidermal auto, allo and xenografts at different cell passages transplanted on burn wound in oryctolagus cuniculus - Halim, Ahmad Sukari (Pusat Pengajian Kesihatan, 2016)
The goal of this study was to investigate the wound healing potential using primary epidermal auto-, allo-, and xenografts in rabbit ( Oryctolagus cuniculus). In this study, rabbit and rat skins were harvested and cultured in vitro. Cultured epithelial autograft, allograft and xenograft cells were sprayed onto the three freshly created wounds with one wound acting as a control. The wounds were monitored every two days for four weeks. After four weeks, the rabbits were euthanized; skin biopsies were taken from each healed wound and subjected to hematoxylin and eosin staining followed by immunohistochemical staining using Pancytokeratin, PCK-26 (Abeam, Germany) and Cytokeratin A1/A3 antibodies. All the examined grafts showed favorable healing outcomes because the wounds appeared similar to normal skin upon healing. The only observed difference was related to the thickness of the epidermis layer in the case of the xenograft transplant, which was thinner compared with the autograft and allograft. It was also noted that the healing rates of the wounds treated with the xenograft was similar to wounds treated with autograft and allografts. The level of antigenicity of the 3 grafts appeared to be the same, which is displayed by the similar healing rate of the grafts.